Relationship between postural and kinesthetic awareness, static balance, and weight-bearing asymmetry in individuals with chronic stroke: A cross-sectional study - Mohammad A. ALMohiza; Ravi Shankar Reddy (PLoS ONE, 2026)
Postural and kinesthetic awareness are essential sensory-perceptual components contributing to balance control and symmetrical weight distribution. In individuals with chronic stroke, deficits in body awareness can impair postural stability and increase asymmetry, yet their precise relationships with balance parameters remain insufficiently explored. This cross-sectional study investigated the associations between postural and kinesthetic awareness and both static balance performance and weight-bearing asymmetry in individuals with chronic stroke. Forty-eight participants who were at least six months post-stroke were assessed using the Postural Awareness Scale (PAS), and joint position sense error was measured via a digital inclinometer. Static balance parameters, including center of pressure (COP), sway area, path length, and sway velocity, were evaluated using a stabilometric force platform. Weight-bearing asymmetry (WBA) was calculated using the two-scale method. Pearson’s correlations and multiple linear regression analyses were conducted. Postural awareness was significantly negatively correlated with sway area (r = –0.53, p = 0.001) and sway velocity (r = –0.51, p = 0.002), while joint position sense error was positively correlated with these metrics (r = 0.47–0.49, p < 0.01). Both awareness measures were significantly associated with WBA (PAS: r = –0.49; joint position error: r = 0.48, p < 0.01). Regression analyses identified PAS as a significant predictor of sway area (β = –0.38, p = 0.002) and WBA (β = –0.36, p = 0.003), while joint position sense error significantly predicted sway velocity (β = 0.41, p = 0.001). These findings highlight the independent associations of postural and kinesthetic awareness with postural control and symmetry in individuals with chronic stroke, suggesting their potential relevance for rehabilitation strategies aimed at improving balance and functional stability.